Network Pharmacology Analysis of Secondary Metabolites of Ciplukan (Physalis angulata L.) Against Lung Cancer - Khoirunnisa, Azka; Jamil, Ahmad Shobrun; Muchlisin, Muhammad Artabah (Majalah Farmaseutik, 2024)
Lung cancer is the most common and high-risk type of cancer. Ciplukan (Physalis angulata L.) has antibacterial, anti-inflammatory, and anticancer activities, as well as cytotoxic ability and inhibits cancer cell growth. Research that discusses the molecular cellular mechanism of P. angulata's potential as an anti-lung cancer has not been widely informed, especially on the network pharmacology aspect of this plant's active compounds. This study reveals the prediction of the molecular mechanism of active compounds of P. angulata as anti-lung cancer using several tools including: Compound database retrieval with Knapsack and PubChem. Absorption Distribution Metabolism and Excretion (ADME) screening with SwissADME. Target protein identification with Gene Card, SwissTargetPrediction and Venny Diagram. Network pharmacology construction with String-DB and Cytoscape. Network pharmacology analysis using Gene Ontology (GO), and Cellular Component and Molecular Function. Based on the results of the analysis of P. angulata protein potential based on Maximal Clique Centrality (MCC) on CytoHubba in Cytoscape application, it shows that the Protein-protein Interaction (PPI) network has 10 main targets, namely ERBB2, KRAS, TP53, PTEN, CDKN2A, NRAS, PIK3CA, BRAF, NF1, and EGFR which interact with each other to regulate cell growth, differentiation, and survival. The results of this study can be concluded that the secondary metabolite compounds of P. angulata have the potential to control and alternative for lung cancer therapy.